Implementasi Algoritme Fuzzy Tsukamoto untuk Penilaian Kinerja Pegawai PT. Bank Tabungan Negara (Persero) Divisi CCRD (Consumer Collection & Remedial Division) - Muhammad Resna; Nurul Hidayat; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Employees are people who work in a company by getting a salary (wage) from the company. The employees performance is the work of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. So that every company needs assessment of performance for the company to evaluate the performance of each employee in every month. At Bank Tabungan Negara (Persero) company, the CCRD division (Consumer Collection & Remedial Division) still uses the Microsoft Excel scoring system so that a system that can facilitate leaders to assess employee performance and provide a more accurate assessment are needed. The solution for making this system is by using the Fuzzy Tsukamoto method. Fuzzy Tsukamoto is used to calculate the rating of each employee in each position. Based on the accuracy testing that has been done, from 50 Skip Tracer position test data, 30 Assistant Field Collector position test data, 10 Field Collector position test data, 8 Skip Tracer Coordinator position test data, 10 Team Leader Field Collector position test data, 5 Collective Staff position test data, and 5 Branch Coordinator position test data. So from the test data, Branch Coordinator positions get accuracy of 86%, Branch Coordinator positions by 76%, Field Collector positions by 70%, Skip Tracer Coordinator positions by 75%, Team Leader Field Collector positions by 90%, Team Leader Field Collector positions by 60%, and Branch Coordinator positions by 80%.